A method for preparing high-strength ceramic pellets
Patent Information
- Application Number
- CN202511313269.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-15
AI Technical Summary
目前,磷石膏和钛石膏的有效利用率较低,多数只能被堆放处理,不仅占用大量土地,还会对环境造成污染
本发明提出了一种高强陶粒的制备方法,以砖粉为硅质原料,拜耳法赤泥为铝质原料,磷石膏和钛石膏作为钙质原料制备建筑陶粒,既可以打破资源约束,又能够减轻环境压力,但是磷石膏和钛石膏中氯离子的溶出,不仅影响陶粒的强度及耐水性能,对钢筋的腐蚀作用还会严重影响建筑结构的耐久性和安全性,而且所制备陶粒的强度也难以满足使用需求。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials, specifically to a method for preparing high-strength ceramsite. Background Technology
[0002] Phosphogypsum is a solid waste generated in the wet-process phosphoric acid production, while titanium gypsum is a precipitate produced when adding alkaline substances to neutralize acidic wastewater during the sulfuric acid process for titanium dioxide production. Currently, the effective utilization rate of phosphogypsum and titanium gypsum is low, and most of them can only be disposed of by stockpiling, which not only occupies a large amount of land but also pollutes the environment.
[0003] Using phosphogypsum and titanium gypsum as raw materials to prepare building ceramsite can break resource constraints and reduce environmental pressure. However, the leaching of chloride ions from phosphogypsum and titanium gypsum not only affects the strength and water resistance of ceramsite, but also seriously affects the durability and safety of building structures due to the corrosion of steel bars. Moreover, the strength of the prepared ceramsite is difficult to meet the application requirements. Summary of the Invention
[0004] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes a method for preparing high-strength ceramsite.
[0005] The technical solution adopted is as follows: A method for preparing high-strength ceramsite is as follows: Brick powder, Bayer red mud, phosphogypsum, and titanium gypsum are mixed to obtain a mixed powder. A binder is added, and the mixture is mixed to form raw material balls. A transition layer and a shell layer are then formed on the surface of the raw material balls. After drying, the mixture is sintered and cooled. The transition layer consists of the following components: Vanadium-titanium iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, borax; The shell is composed of the following components: Vanadium-titanium iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride.
[0006] Furthermore, the mass ratio of the brick powder, Bayer red mud, phosphogypsum, and titanium gypsum is 1-3:1-3:0.5-1:0.5-1.
[0007] Furthermore, the mass ratio of vanadium-titanium iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax in the transition layer composition is 20-40:20-40:1-5:1-5:1-5:0.1-1.
[0008] Furthermore, the mass ratio of vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride in the shell composition is 40-60:40-60:1-3:3-6.
[0009] Furthermore, the adhesive is an aqueous solution of polyvinyl alcohol.
[0010] Furthermore, the solid-liquid mass ratio of the mixed powder to the binder is 1:0.1-0.2.
[0011] Furthermore, during the preparation of the transition layer, a wet ball mill is used to prepare a slurry from vanadium-titanium iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax. The raw material balls are then impregnated in the slurry to coat the material, followed by drying.
[0012] Furthermore, during shell preparation, a wet ball mill is used to prepare a slurry from vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride. The raw material balls are then impregnated in the slurry to coat the shell, followed by drying.
[0013] Furthermore, the mass percentage of V2O5 in the vanadium-titanium iron tailings powder is ≥0.5%.
[0014] Furthermore, the sintering temperature is 1200-1250℃.
[0015] The beneficial effects of this invention are: This invention proposes a method for preparing high-strength expanded clay aggregate, using brick powder as a siliceous raw material, Bayer red mud as an aluminous raw material, and phosphogypsum and titanium gypsum as calcareous raw materials to prepare building expanded clay aggregate. This method can break resource constraints and reduce environmental pressure. However, the dissolution of chloride ions from phosphogypsum and titanium gypsum not only affects the strength and water resistance of the expanded clay aggregate, but also seriously affects the durability and safety of building structures due to its corrosive effect on steel bars. Moreover, the strength of the prepared expanded clay aggregate is difficult to meet the application requirements.
[0016] This invention utilizes a core-shell structure design. The shell coating effectively prevents chloride ion leaching and also significantly improves the mechanical strength of the ceramsite while reducing water absorption. The vanadium-titanium-iron tailings powder in the shell provides the basic mineral composition, ensuring the shell's mechanical strength and stability. Fly ash provides active SiO2 and Al2O3, forming a glassy phase at high temperatures that fills surface pores, enhancing density and strength. Furthermore, the combined action of V2O5 and aluminum fluoride in the vanadium-titanium-iron tailings powder generates mullite whiskers, further increasing the mechanical strength of the ceramsite shell. Calcium fluoride acts as a flux, significantly lowering the sintering temperature of the shell material, promoting liquid phase formation, and optimizing the sintering process.
[0017] Because the raw material pellets generate a large amount of gas during sintering, the expansion rates of the shell and core are difficult to match, which can easily cause the shell to crack and reduce the strength of the ceramic pellets. This invention designs a transition layer between the shell and core. The transition layer can generate a large amount of liquid phase during sintering and react with the shell and core to tightly bond them together and provide stress buffer. This gradient design can better match the performance between each layer, reduce internal stress, and thus achieve higher overall strength. The vanadium-titanium-iron tailings powder and fly ash in the transition layer can participate in the reaction during the shell sintering process. Calcium oxide can provide an alkaline environment, stimulate the potential activity of materials such as fly ash, and act as a fluxing component to lower the melting temperature. It can also react with the raw material pellets to generate chloride-containing compounds, which can improve the bonding strength and solidify chloride ions. Potassium feldspar, sodium feldspar, and borax synergistically lower the melting temperature of the system, accelerate the formation of the glass phase, and promote the bonding between the shell and core.
[0018] The ceramsite prepared by this invention not only has low water absorption but also excellent mechanical strength. Its core-shell structure can effectively inhibit the release of chloride ions, making full use of solid waste, reducing environmental pressure, and turning waste into treasure. It achieves two goals at once and has certain social, economic and ecological benefits. Detailed Implementation
[0019] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0020] Brick powder: Taken from construction waste disposal sites, crushed and screened, its chemical composition is shown in the table below: Bayer process red mud: taken from the red mud stockpile of the aluminum plant, its chemical composition is shown in the table below: Phosphogypsum: Sourced from Hunan Bazhou Phosphate Chemical Technology Co., Ltd., its chemical composition is shown in the table below: Titanium gypsum: sourced from Hunan Xinhongda Vanadium Industry Co., Ltd., its chemical composition is shown in the table below: Vanadium-titanium-iron tailings powder: sourced from Hunan Xinhongda Vanadium Industry Co., Ltd., its chemical composition is shown in the table below: Fly ash: Grade 1, purchased from Hebei Huishun Mining Co., Ltd.
[0021] Calcium oxide: purity ≥99%, purchased from Langfang Qianyao Technology Co., Ltd.
[0022] Potassium feldspar: Purchased from Tianjin Hongqiao District Tianbao Haotong Stone Processing Plant.
[0023] Sodium feldspar: Purchased from Tianjin Hongqiao District Tianbao Haotong Stone Processing Plant.
[0024] Borax: Purchased from Shandong Zhuoxuan New Materials Co., Ltd.
[0025] Aluminum fluoride: purchased from Langfang Qianyao Technology Co., Ltd.
[0026] Calcium fluoride: purchased from Langfang Qianyao Technology Co., Ltd.
[0027] Example 1: A method for preparing high-strength ceramsite: Weigh and dry each raw material thoroughly. Mix brick powder, Bayer red mud, phosphogypsum, and titanium gypsum in a mass ratio of 2:2:0.5:0.5 to obtain a mixed powder. Add a 5% polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.15. After mixing in a pelletizing machine, produce raw material pellets with a diameter of 10±1mm. Vanadium-titanium-iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax were mixed evenly in a mass ratio of 30:30:3:2:2:0.2 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium, a solid-liquid mass ratio of 1:1, and sodium hexametaphosphate as the dispersant. The amount of sodium hexametaphosphate was 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The raw material balls were immersed in the slurry for 5 minutes at room temperature, drained, and then dried in an oven at 100℃ for 5 hours to obtain ball blanks. Vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride were mixed evenly in a mass ratio of 50:50:2:5 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The billet was immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated its surface. Subsequently, it was dried in an oven at 100℃ for 5 hours, and then sintered in a sintering furnace at a rate of 1℃ / min to 1230℃ for 2 hours. After that, it was naturally cooled to room temperature with the furnace.
[0028] Example 2: A method for preparing high-strength ceramsite: Weigh and thoroughly dry all raw materials. Mix brick powder, Bayer red mud, phosphogypsum, and titanium gypsum in a mass ratio of 3:3:1:1 to obtain a mixed powder. Add a 5% (w / w) polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.2. Mix thoroughly in a pelletizer to form raw material pellets with a diameter of 10±1 mm. Mix vanadium-titanium-iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax in a mass ratio of 40:40:5:5:5:1 to obtain a mixed powder. Add the mixed powder to a ball mill jar, using water as the milling medium, a solid-liquid mass ratio of 1:1, and sodium hexametaphosphate as the dispersant (2.5% of the mixed powder mass). Mill for 5 hours to obtain a slurry. Immerse the raw material pellets in the slurry at room temperature for 5 minutes, drain, and then dry in a 100℃ oven for 5 hours to obtain pellet blanks. Vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride were mixed evenly in a mass ratio of 60:60:3:6 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The billet was immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated its surface. Subsequently, it was dried in an oven at 100℃ for 5 hours, and then sintered in a sintering furnace at a rate of 1℃ / min to 1250℃ for 2 hours. After that, it was naturally cooled to room temperature with the furnace.
[0029] Example 3: A method for preparing high-strength ceramsite: Weigh and dry each raw material thoroughly. Mix brick powder, Bayer red mud, phosphogypsum, and titanium gypsum in a mass ratio of 1:1:0.5:0.5 to obtain a mixed powder. Add a 5% polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.2. Mix the powder in a pelletizing machine to form raw material balls with a diameter of 10±1mm. Vanadium-titanium-iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax were mixed evenly in a mass ratio of 20:20:1:1:1:0.1 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium, a solid-liquid mass ratio of 1:1, and sodium hexametaphosphate as the dispersant. The amount of sodium hexametaphosphate was 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The raw material balls were immersed in the slurry for 5 minutes at room temperature, drained, and then dried in an oven at 100℃ for 5 hours to obtain ball blanks. Vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride were mixed evenly in a mass ratio of 40:40:1:3 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The billet was immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated its surface. Subsequently, it was dried in an oven at 100℃ for 5 hours, and then sintered in a sintering furnace at a rate of 1℃ / min to 1200℃ for 2 hours. After that, it was naturally cooled to room temperature with the furnace.
[0030] Comparative Example 1: It is basically the same as Example 1, except that it does not contain a transition layer.
[0031] A method for preparing high-strength ceramsite: Weigh and dry each raw material thoroughly. Mix brick powder, Bayer red mud, phosphogypsum, and titanium gypsum in a mass ratio of 2:2:0.5:0.5 to obtain a mixed powder. Add a 5% polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.15. After mixing in a pelletizing machine, produce raw material pellets with a diameter of 10±1mm. Vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride were mixed evenly in a mass ratio of 50:50:2:5 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The raw material balls were immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated their surface. Subsequently, the balls were dried in an oven at 100℃ for 5 hours. The sintering process was carried out in a sintering furnace at a rate of 1℃ / min to 1230℃ for 2 hours, and then allowed to cool naturally to room temperature with the furnace.
[0032] Comparative Example 2: It is basically the same as Example 1, except that iron tailings powder is used instead of vanadium-titanium iron tailings powder.
[0033] Iron tailings powder originated from an iron mine in Hunan Province, and its chemical composition is shown in the table below: A method for preparing high-strength ceramsite: Weigh and dry each raw material thoroughly. Mix brick powder, Bayer red mud, phosphogypsum, and titanium gypsum in a mass ratio of 2:2:0.5:0.5 to obtain a mixed powder. Add a 5% polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.15. After mixing in a pelletizing machine, produce raw material pellets with a diameter of 10±1mm. Iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax were mixed evenly in a mass ratio of 30:30:3:2:2:0.2 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium, a solid-liquid mass ratio of 1:1, and sodium hexametaphosphate as the dispersant. The amount of sodium hexametaphosphate was 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. Raw material balls were immersed in the slurry for 5 minutes at room temperature, drained, and then dried in an oven at 100℃ for 5 hours to obtain ball blanks. Iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride were mixed evenly in a mass ratio of 50:50:2:5 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The billet was immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated its surface. Subsequently, it was dried in an oven at 100℃ for 5 hours, and then sintered in a sintering furnace at a rate of 1℃ / min to 1230℃ for 2 hours. After that, it was naturally cooled to room temperature with the furnace.
[0034] Comparative Example 3: It is basically the same as Example 1, except that phosphogypsum is used instead of titanium gypsum.
[0035] A method for preparing high-strength ceramsite: Weigh and thoroughly dry all raw materials. Mix brick powder, Bayer red mud, and phosphogypsum in a mass ratio of 2:2:1 to obtain a mixed powder. Add a 5% (w / w) polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.15. After mixing in a pelletizer, form raw material balls with a diameter of 10±1 mm. Mix vanadium-titanium-iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax in a mass ratio of 30:30:3:2:2:0.2 to obtain a mixed powder. Add the mixed powder to a ball mill jar, using water as the milling medium, a solid-liquid mass ratio of 1:1, and sodium hexametaphosphate as a dispersant at 2.5% of the mixed powder mass. After milling for 5 hours, obtain a slurry. Immerse the raw material balls in the slurry at room temperature for 5 minutes, drain the water, and dry in a 100℃ oven for 5 hours to obtain pellet blanks. Vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride were mixed evenly in a mass ratio of 50:50:2:5 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The billet was immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated its surface. Subsequently, it was dried in an oven at 100℃ for 5 hours, and then sintered in a sintering furnace at a rate of 1℃ / min to 1230℃ for 2 hours. After that, it was naturally cooled to room temperature with the furnace.
[0036] Comparative Example 4: It is basically the same as Example 1, except that titanium plaster is used instead of phosphogypsum.
[0037] A method for preparing high-strength ceramsite: Weigh and thoroughly dry all raw materials. Mix brick powder, Bayer red mud, and titanium gypsum in a mass ratio of 2:2:1 to obtain a mixed powder. Add a 5% (w / w) polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.15. After mixing in a pelletizer, form raw material balls with a diameter of 10±1 mm. Mix vanadium-titanium-iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax in a mass ratio of 30:30:3:2:2:0.2 to obtain a mixed powder. Add the mixed powder to a ball mill jar, using water as the milling medium, a solid-liquid mass ratio of 1:1, and sodium hexametaphosphate as a dispersant at 2.5% of the mixed powder mass. After milling for 5 hours, obtain a slurry. Immerse the raw material balls in the slurry at room temperature for 5 minutes, drain the water, and dry in a 100℃ oven for 5 hours to obtain pellet blanks. Vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride were mixed evenly in a mass ratio of 50:50:2:5 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The billet was immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated its surface. Subsequently, it was dried in an oven at 100℃ for 5 hours, and then sintered in a sintering furnace at a rate of 1℃ / min to 1230℃ for 2 hours. After that, it was naturally cooled to room temperature with the furnace.
[0038] Comparative Example 5: It is basically the same as Example 1, except that aluminum fluoride is not added.
[0039] A method for preparing high-strength ceramsite: Weigh and dry each raw material thoroughly. Mix brick powder, Bayer red mud, phosphogypsum, and titanium gypsum in a mass ratio of 2:2:0.5:0.5 to obtain a mixed powder. Add a 5% polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.15. After mixing in a pelletizing machine, produce raw material pellets with a diameter of 10±1mm. Vanadium-titanium-iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax were mixed evenly in a mass ratio of 30:30:3:2:2:0.2 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium, a solid-liquid mass ratio of 1:1, and sodium hexametaphosphate as the dispersant. The amount of sodium hexametaphosphate was 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The raw material balls were immersed in the slurry for 5 minutes at room temperature, drained, and then dried in an oven at 100℃ for 5 hours to obtain ball blanks. Vanadium-titanium-iron tailings powder, fly ash, and calcium fluoride were mixed evenly in a mass ratio of 50:50:5 to obtain a mixed powder. The mixed powder was added to a ball mill jar, with water as the ball milling medium and a solid-liquid mass ratio of 1:1. Sodium hexametaphosphate was used as the dispersant, with the amount of sodium hexametaphosphate being 2.5% of the mass of the mixed powder. After ball milling for 5 hours, a slurry was obtained. The billet was immersed in the slurry for 5 minutes at room temperature, removed and drained, and then immersed again for 5 minutes to ensure that the slurry fully coated its surface. Subsequently, it was dried in an oven at 100℃ for 5 hours, and then sintered in a sintering furnace at a rate of 1℃ / min to 1230℃ for 2 hours. After that, it was naturally cooled to room temperature with the furnace.
[0040] Comparative Example 6: It is basically the same as Example 1, except that the raw material balls are sintered directly.
[0041] A method for preparing high-strength ceramsite: Weigh and thoroughly dry all raw materials. Mix brick powder, Bayer red mud, phosphogypsum, and titanium gypsum in a mass ratio of 2:2:0.5:0.5 to obtain a mixed powder. Add a 5% (w / w) polyvinyl alcohol aqueous solution as a binder to the mixed powder at a solid-liquid mass ratio of 1:0.15. After mixing in a pelletizing machine, form raw material pellets with a diameter of 10±1 mm. Dry the raw material pellets in a 100℃ oven for 5 hours, then sinter them in a sintering furnace at a temperature increased to 1230℃ at a rate of 1℃ / min for 2 hours. Allow them to cool naturally to room temperature in the furnace.
[0042] Performance testing: The high-strength ceramsite prepared in Examples 1-3 and Comparative Examples 1-6 of this invention was used as samples for performance testing.
[0043] The bulk density, water absorption and cylinder compressive strength of the samples were determined in accordance with the "Lightweight Aggregates and Their Test Methods" (GB / T17431.1-2010, GB / T17431.2-2010).
[0044] The sample was added to water at a solid-liquid mass ratio of 1:10, and the leachate was prepared according to the method in "Leaching Toxicity of Solid Waste - Horizontal Oscillation Method" (GB 5086.2-1997). The concentration of chloride ions in the leachate was determined using a CLS-10A portable chloride meter.
[0045] The test results are shown in Table 1 below: Table 1: As shown in Table 1 above, the ceramsite prepared by this invention has low water absorption and excellent mechanical strength, and the core-shell structure can effectively inhibit the release of chloride ions.
[0046] As can be seen from the comparison between Example 1 and Comparative Example 1, the transition layer can greatly reduce the water absorption rate of ceramsite and improve its mechanical strength.
[0047] As can be seen from the comparison between Example 1 and Comparative Example 2, compared with iron tailings powder, the vanadium-titanium iron tailings powder used in this invention can effectively reduce the water absorption rate of ceramsite and improve its mechanical strength.
[0048] As can be seen from the comparison between Example 1 and Comparative Examples 3-4, the combined use of phosphogypsum and titanium gypsum plays a positive role in reducing the water absorption rate of ceramsite and improving its mechanical strength.
[0049] As can be seen from the comparison between Example 1 and Comparative Example 5, the addition of aluminum fluoride can effectively reduce the water absorption rate of ceramsite and improve its mechanical strength.
[0050] As can be seen from the comparison between Example 1 and Comparative Example 6, the core-shell structure greatly reduces the water absorption rate of the ceramsite, improves its mechanical strength, and effectively inhibits the release of chloride ions.
[0051] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing high-strength ceramsite, characterized in that, Specifically as follows: Brick powder, Bayer red mud, phosphogypsum, and titanium gypsum are mixed to obtain a mixed powder. A binder is added and mixed to form raw material balls. A transition layer and a shell layer are then formed on the surface of the raw material balls. After drying, the mixture is sintered and cooled. The transition layer consists of the following components: Vanadium-titanium iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, borax; The shell is composed of the following components: Vanadium-titanium iron tailings powder, fly ash, aluminum fluoride, calcium fluoride; The mass ratio of brick powder, Bayer red mud, phosphogypsum, and titanium gypsum is 1-3:1-3:0.5-1:0.5-1; The mass ratio of vanadium-titanium iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax in the transition layer composition is 20-40:20-40:1-5:1-5:1-5:0.1-1. The mass ratio of vanadium-titanium iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride in the shell composition is 40-60:40-60:1-3:3-6.
2. The method for preparing high-strength ceramsite as described in claim 1, characterized in that, The adhesive is an aqueous solution of polyvinyl alcohol.
3. The method for preparing high-strength ceramsite as described in claim 1, characterized in that, The solid-liquid mass ratio of the mixed powder to the binder is 1:0.1-0.
2.
4. The method for preparing high-strength ceramsite as described in claim 1, characterized in that, During the preparation of the transition layer, vanadium-titanium iron tailings powder, fly ash, calcium oxide, potassium feldspar, sodium feldspar, and borax are made into a slurry by wet ball milling. The raw material balls are then impregnated in the slurry to coat the material, and then dried.
5. The method for preparing high-strength ceramsite as described in claim 4, characterized in that, During shell preparation, vanadium-titanium-iron tailings powder, fly ash, aluminum fluoride, and calcium fluoride are made into a slurry by wet ball milling. The raw material balls are then impregnated in the slurry to coat the shell, and then dried.
6. The method for preparing high-strength ceramsite as described in claim 1, characterized in that, The mass percentage of V2O5 in the vanadium-titanium iron tailings powder is ≥0.5%.
7. The method for preparing high-strength ceramsite as described in claim 1, characterized in that, The sintering temperature is 1200-1250℃.
Citation Information
Patent Citations
Preparation method and application of high-doping-amount red mud-based maritime work cementing material
CN122541116A